DISCRIMINATION OF RELIGIOUS FREEDOM: The Case of Persecution of the Ahmadiyya Minority Group in West Kalimantan - Bibi Suprianto; Syarifah Ema Rahmaniah; Andi Alfian; Sopian Lubis (IAIN Ponorogo, 2023)
Human rights are an aspect of social existence. Human rights also include the right to religious freedom in retaining faith and belief in human beings. By comprehending the right to religious freedom, we may identify the rights of belief in all individuals. This study aims to inform readers about the Ahmadiyya minority group’s religious freedom abuses in West Kalimantan due to discriminatory policies. This study argues that Ahmadiyya in Sintang has encountered forms of discrimination against the rights to religious freedom in Indonesia.Thus, this study formulates research questions such as (1) what is the chronology and form of persecution against Ahmadiyya? (2) what is the role of actors in discriminating against the Ahmadiyya minority group in West Kalimantan? (3) What is the policy on religious freedom toward the Ahmadiyya minority group in West Kalimantan? This study employed qualitative methods to describe the chronology of Ahmadiyya events in West Kalimantan through interviews and documentation. The findings of the study indicate that religious freedom discrimination against Ahmadiyya in West Kalimantan demonstrates: 1) the existence of violations of the right to freedom of religion; 2) the existence of contradictory policies; and 3) the existence of religiously motivated violence in West Kalimantan. This study’s findings demonstrate that the violation of religious freedom against the Ahmadiyya in West Kalimantan is a type of religious-based discrimination.